Art déco 1910-1939 / red. Charlotte Benton, Tim Benton i Ghislaine Wood ; przekł. Jerzy Łoziński, Tomasz Rosiński, Maria Szybińska. - Łoziński, Jerzy (1947- ).; Rosiński, Tomasz; Szybińska, Maria (Zysk i S-ka Wydawnictwo, 2010)
Katalog wystawy: Victoria and Albert Museum, Londyn, 27 marzec - 20 lipiec 2003.